Improving the Morals of Karimah Santri at Al-Ihsan Islamic Boarding School - Milah, Hilyatul; Regina, Mileandi Indra; Tarsono, Tarsono (Jurnal Inovasi Pendidikan Agama Islam (JIPAI), 2023)
An effective learning environment is a very important factor in the educational process to achieve educational goals. Akhlakul Karimah is the goal to be achieved in the Islamic education process. Islamic boarding schools are educational institutions that function as institutions for spreading and developing Islamic religious knowledge as well as institutions that function as producers of national cadres who have good norms and values. So, Islamic boarding schools must be designed in such a way that they can function as they should. This research aims to determine the environment of the Al Ihsan Islamic Boarding School as an effective environment in improving the morals and morals of students. The approach used is a qualitative approach. The methods used in this research are observation and interviews. The location of this research is the Al Ihsan Islamic Boarding School. The research results show that physically Al Ihsan is a clean, comfortable, safe, and beautiful Islamic boarding school. Socially, Al Ihsan and his students have a spirit of justice, responsibility, and cooperation. In terms of social systems, it has a good administrative system. Culturally, the institution created is very good, this can be seen from the material which is a combination of traditional books and contemporary books which makes Al Ihsan students literate in moderate modern sciences and a different organizational culture which will lead the students to achieve noble morals.